Source characterization of volatile organic compounds in the Colorado Northern Front Range Metropolitan Area during spring and summer 2015. Issue 6 (17th March 2017) - Abeleira, A.; Pollack, I. B.; Sive, B.; Zhou, Y.; Fischer, E. V.; Farmer, D. K.
Abstract: Hourly measurements of 46 volatile organic compounds (VOCs) from the Boulder Atmospheric Observatory in Erie, CO, were collected over 16 weeks in spring and summer 2015. Average VOC reactivity (1.2 s −1 in spring and 2.4 s −1 in summer) was lower than most other U.S. urban sites. Positive matrix factorization analysis identified five VOC factors in the spring, corresponding to sources from (1) long‐lived oil and natural gas (ONG‐long lived), (2) short‐lived oil and natural gas (ONG‐short lived), (3) traffic, (4) background, and (5) secondary chemical production. In the summer, an additional biogenic factor was dominated by isoprene. While ONG‐related VOCs were the single largest contributor (40–60%) to the calculated VOC reactivity with hydroxyl radicals (OH) throughout the morning in both spring and summer, the biogenic factor substantially enhanced afternoon and evening (2–10 P.M. local time) VOC reactivity (average of 21%; maxima of 49% of VOC reactivity) during summertime. These results contrast with a previous summer 2012 campaign which showed that biogenics contributed only 8% of VOC reactivity on average. The interannual differences suggest that the role of biogenic VOCs in the Colorado Northern Front Range Metropolitan Area (NFRMA) varies with environmental conditions such as drought stress. Overall, the NFRMA was more strongly influenced by ONG sources of VOCs than other urban and suburban regions in the U.S. Key Points: Oil and natural gas development was the largest source of observed VOC reactivity in the Colorado Front Range in spring 2015 Observed VOC reactivity in the Colorado Front Range in summer 2015 was low (average = 2.4 s −1 ) relative to other urban areas in the U.S. Isoprene contributed substantially to VOC reactivity in summer 2015, in contrast to a previous study